Implementation of Telemedicine in Indonesian Urology Practice During COVID-19 Pandemic: a National Survey: a National Survey - Wiseso, Faridz Albam; Hendri, Ahmad Zulfan; Brodjonegoro, Sakti Ronggowardhana (Urology Journal, 2021)
Background: The pandemic of COVID-19 is nowhere from over, which pushes us to adapt to it. Social distancing rules were applied to restrict the people and prevent virus transmission. Despite these restrictions, the patient's care should not be compromised. Doctors are encouraged to technologically improve themselves to get used to the utilization of telemedicine. Methods: We conducted an online survey of urology specialists and urology residents throughout the country. The survey was accompanied by the Indonesian Urological Association, and the survey was opened for one month and sent by email to all members of the association. Results: A total of 50 urologists and 182 urology residents participated. Almost half (48%) currently do not have facilities to hold a telemedicine practice in their institution, and 14% reported inadequate facilities. The majority reveals that the barrier to conducting this method was due to insufficient facility. Other issues like insurance coverage and patient's interest in telemedicine, the risk of patient's data leak, and the urologist's lack of interest in telemedicine might also be challenging. Despite some doubts, in sum, more than half have thought that telemedicine would keep utilized although the pandemic is resolved. Conclusions: We are currently learning the novel telemedicine implementation and some challenges still need to be resolved. Starting from the regulation and legal protection fundamentally, and the health insurance coverage needs to be determined. After all, the low interest in adopting this method has become the greatest barrier.